Using knowledge networks to teach online writing skills in the professional writing classroom - Robertson, Rachel (Curtin University, 2012)
Recent research shows that online knowledge networks can be effective learning tools. The aim of this project was to determine the value of knowledge networking in classes where students have minimal experience (and low confidence) in online environments; and where the web is both the learning environment and the object of their learning. In Writing and Research for Professional Contexts 311, students learn to research, write, and edit web-based material in preparation for the workplace. This project introduced and evaluated three new assessment tasks that exploited knowledge networking in developing student skills in online writing genres.